Новые методы геоинформатики мониторинга волновых полей в иерархических средах - Хачай, О.А.; Хачай, О.Ю.; Хачай, А.Ю. (Геоінформатика, 2015)
Построен алгоритм 3D моделирования электромагнитного поля для произвольного типа источника возбуждения N-слойной среды с иерархическим проводящим включением, расположенным в J-м слое. Построены алгоритмы 2D моделирования для дифракции звука и линейно поляризованной поперечной упругой волны на включении с иерархической структурой, расположенном в J-м слое N-слойной упругой среды. Выписаны уравнения теоретической обратной задачи для 2D электромагнитного поля Е- и H-поляризации и линейно поляризованной упругой волны при возбуждении N-слойной проводящей или упругой среды с иерархическим проводящим или упругим включением, расположенным в υ-м слое. Из построенной теории следует, что при интерпретации данных мониторинга необходимо использовать такие данные, которые получены в рамках систем наблюдения, настроенных на исследование иерархической структуры среды. В случае более сложной среды каждое волновое поле привносит свою информацию о ее внутренней структуре, поэтому интерпретацию сейсмического и электромагнитного поля необходимо вести раздельно, не смешивая эти базы данных. Побудовано алгоритм 3D моделювання електромагнітного поля для довільного типу джерела збудження N-шарового середовища з ієрархічним провідним включенням, розміщеним J-му шарі. Побудовано алгоритми 2D моделювання для дифракції звуку і лінійно поляризованої поперечної пружної хвилі на включенні з ієрархічною структурою, розміщеному в J-му шарі N-шарового пружного середовища. Виписано рівняння теоретичної оберненої задачі для 2D електромагнітного поля Е- і H-поляризації та лінійно поляризованої пружної хвилі під час збудження N-шарового провідного або пружного середовища з ієрархічним провідним або пружним включенням, розташованим у υ-му шарі. З побудованої теорії випливає, що при інтерпретації даних моніторингу необхідно використовувати такі дані, які отримані в межах систем спостереження, настроєних на дослідження ієрархічної структури середовища. В разі складнішої побудови середовища кожне хвильове поле привносить свою інформацію про її внутрішню структуру, тому інтерпретацію сейсмічного та електромагнітного полей необхідно вести окремо, не змішуючи ці бази даних. Purpose. Geological medium is an open system which is influenced by outer and inner factors that can lead it to a unstable state. That non stability as a rule occurs locally and these zones are named dynamically active elements, which are indicators of potential catastrophic sources. These objects differ from the embedded geological medium by their structural forms, which often are of hierarchical type. The process of their activation can be searched, using wave fields monitoring. For that purpose it is necessary to develop new algorithms of modeling wave field’s propagation through the local objects with hierarchical structure. It also requires a theory of interpreting the distribution of wave fields to define the contours of these local hierarchical objects. Design/methodology/approach. We constructed an algorithm for the 3D modeling of an electromagnetic field for an arbitrary type of source of excitation in a N-layered medium with a hierarchic conductive intrusion, located in the layer number J. We also been constructed algorithms for the 2D modeling of sound diffraction and linear polarized transversal seismic wave on an intrusion of the hierarchic structure located in the layer number / of the N-layered elastic medium. We used the method of integral and integral-differential equations for a space frequency presentation of wave field’s distribution. An algorithm is developed to build the equation of the theoretical inverse problem for 2-D electromagnetic field of E and H polarization and linear polarized longitudinal elastic wave by excitation of the N-layered conductive or elastic medium with hierarchic conductive or elastic inclusion located in the v-th layer. Findings. The theory proves that for such complicated medium each wave field contains its own information about the inner structure of the hierarchical inclusion. Therefore it is important to interpret the monitoring data for each wave field apart, without mixing the data base. Practical value/implications. These results will serve as the base for constructing new systems of monitoring observations of dynamical geological systems. It is particularly useful in preventing rock shocks in deep mines by their exploitation.